Paradoksal Karakter dalam Novel Semua Ikan di Langit Karya Ziggy Z dan Analisis Hubungan Manusia dengan Tuhan - Syakrila Ratu Awwali; Mulyono Mulyono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
God and human have a complex relation that often creates paradox. The paradox appears because human being doesn't completely understand God's mean behind His rules. So, in this research, the author will explain paradox of the characters in Semua Ikan di Langit, a novel written by Ziggy Zesyazeoviennazabrizky in reflecting the relation of human and God. The data collection method used in this research is read and note method. Then the data was Analyzed with qualitative method. The result of the research shows that Beliau, a character that resemble God, has a God's power who is omnipotent, but on the other hand, is also not perfect. However, this imperfection occured because Bus Damri and Nad as servants did not fully knowing about Beliau. This imperfection is only a misunderstanding since the servants didn't know Beliau completely. The human relationship with God is also illustrated in the figures of Bus Damri and Nad who represent obedience and betrayal. In addition, the relationship between God and human can occur because human being is reliant on God , which was reflected in the character of the Farmer. Hopefully, this research can be useful for further studies